Defect Structures in Neutron Irradiated 6H-SiC Studied by X-Ray Diffraction Line Profile Analysis - Magerl, Andreas; Hock, Rainer; et al. (Materials Research Society Symposium - Proceedings, 2001)
We have investigated by x-ray diffraction defect structures in 6H-SiC after neutron irradiation with different fluences and followed by different annealing procedures. An interpretation along a model of Klimanek [1,4-6] shows, that higher fluences lead to a stronger than linear reduction of the correlation length, whereas higher annealing temperatures correlate with a better recovery of the correlation length. In addition defects of 1st kind created by irradiation are reduced by annealing. We find that annealing changes the character of the defects and it accentuates a defect structure already present in the original samples.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.LK.defect